Peran Canvasing untuk Mengedukasi Persepsi Negatif Masyarakat terhadap Perusahaan Pialang - Pratama, Reyhan Aditya; Rini, Hesty Prima (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to improve public understanding and reduce negative perceptions toward legally registered brokerage firms. Negative perceptions often arise due to low financial literacy and the widespread occurrence of illegal investment schemes. The program was conducted through direct counseling and socialization activities (canvassing) in collaboration with PT Trijaya Pratama Futures (TPFX) Surabaya. Activities were carried out in public spaces using face-to-face communication, educational material delivery, interactive discussions, and distribution of informational media. The materials focused on brokerage firm legality, futures trading mechanisms, and investment risk awareness. The results indicate that participants gained better understanding and were able to distinguish legal brokerage firms from illegal investments. This program contributes to enhancing financial literacy and strengthening public trust in licensed brokerage institutions.